CONSUMER PERCEPTION ON WOMEN FILM CELEBRITY ENDORSEMENT AND PURCHASE INTENTION (Journal of Pharmaceutical Negative Results, 2023)
The women celebrity endorsements show the times of change by breaking stereotypes. This study deals with the perception of the customers towards the brands that are endorsed by women. The study has been conducted in Chennai city with 127 respondents. Structured Questionnaire was distributed and random sampling has been adopted. The types of product categories and the perception of the customers towards the brands endorsed by women celebrities are explored. Percentage analysis, Factor analysis, mean based ranking, Multiple Regression have been applied using SPSS 23 software. The study shows the most dominant product is Fashion products. The most suitable product category suitable for women endorsement is Packed and Processed foods. The most perceived opinion of the customers towards women brand endorsement is that they have strong and favourable associations with brands, brands fulfils what they promise and customer are able to recall quickly the logo, symbol and colour of the brands that are endorsed by women.